2020
DOI: 10.3390/ijms21030730
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs and lncRNAs in Echinococcus and Echinococcosis

Abstract: Echinococcosis are considered to be potentially lethal zoonotic diseases that cause serious damage to hosts. The metacestode of Echinococcus multilocularis and E. granulosus can result in causing the alveolar and cystic echinococcoses, respectively. Recent studies have shown that non-coding RNAs are widely expressed in Echinococcus spp. and hosts. In this review, the two main types of non-coding RNAs—long non-coding RNAs (lncRNAs) and microRNAs (miRNAs)—and the wide-scale involvement of these molecules in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 107 publications
0
8
0
Order By: Relevance
“…However, the function of the miRNAs miR-71, let-7 and miR-61 was verified, and the target of miR-71 was also confirmed, in total, the targets and biological functions of fifteen miRNAs in Echinococcus species were predicted. 22 Jin et al have investigated miRNA profiling in the mice in response to E multilocularis infection. They reported that miR-21a-5p, miR-101b-3p, miR-122-5p, miR-192-5p, let-7a, b, c and f are common in liver tissue samples and decrease in host during infestation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the function of the miRNAs miR-71, let-7 and miR-61 was verified, and the target of miR-71 was also confirmed, in total, the targets and biological functions of fifteen miRNAs in Echinococcus species were predicted. 22 Jin et al have investigated miRNA profiling in the mice in response to E multilocularis infection. They reported that miR-21a-5p, miR-101b-3p, miR-122-5p, miR-192-5p, let-7a, b, c and f are common in liver tissue samples and decrease in host during infestation.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, human echinococcosis poses a significant burden on patients and health care. The life cycle of Echinococcus consists of three stages: egg, larva, and adult (see [ 2 – 6 ]). Adults reside in the definitive hosts (mainly dogs), produce eggs that are passed in the feces, contaminate the environment (for example, water, dog's fur, vegetables, grass, and soil), and are immediately infectious.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that circulating non-coding RNAs, including miRNAs and lncRNAs, can be detected in the blood of hosts infected with E. granulosus and Echinococcus multilocularis. 29 These stably circulating non-coding RNAs may play significant roles in the establishment and development of host-parasite interactions and could serve as diagnostic markers and therapeutic targets. However, the circRNA expression profiles in CE have been poorly explored.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, reduced miR-19b levels promote pericystic tissue formation during CE by inducing fibrosis through increased expression of TβRII, activation of hepatic stellate cells, and production of ECM 30. A previous report highlighted the differentially expressed lncRNAs and mRNAs between splenic monocytic myeloid-derived suppressor cells of E. granulosus protoscolex-infected mice and normal mice 29. Further research on the functional mechanisms suggested that lncRNAs play a role in the immune response of the intermediate hosts,mice, against E. granulosus and might be useful as specific biomarkers for CE 29.…”
mentioning
confidence: 97%
See 1 more Smart Citation